TAX AVOIDANCE PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputri, Reniar; Nuswandari, Cahyani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study is based on agency theory and its application in tax research, where this study examines the effect of institutional ownership, audit committees, leverage, and company size on tax avoidance. The research sample is a company in the energy sector with a research period of 2019 – 2021. Multiple regression analysis was applied to test the research hypothesis. The test results show, institutional ownership has a positive significant effect on tax avoidance, while the audit committee, leverage, and company size do not show significant effects on tax avoidance.